2014
DOI: 10.4103/2249-4863.130254
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and it′s Relation to Diabetic Control in a Primary Care Setting

Abstract: Context:Patient satisfaction is of increasing importance and recognized as an important indicator for quality of care. It is influenced by the patients, physicians and practice's characteristics. The literature on diabetes has increasingly focused on the quality of care and its measurement. The relationship between the quality of diabetes care and patient satisfaction is poorly understood and it requires further elaboration.Aims:The aim of this study is to Identify the underlying factors influencing patient's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 27 publications
(31 reference statements)
5
32
1
4
Order By: Relevance
“…Students reported that they gained a tremendous amount from the exercise; they particularly enjoyed the real patients, immediate feedback, and multiple opportunities to practice. It is important that medical students practice communication skills as evidence shows that perceptions of good communication between patients and physicians improve patient satisfaction 38. In addition, patients want autonomy and a role in determination of their medical care; physicians need to be able to understand the goals and needs of patients 14,15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students reported that they gained a tremendous amount from the exercise; they particularly enjoyed the real patients, immediate feedback, and multiple opportunities to practice. It is important that medical students practice communication skills as evidence shows that perceptions of good communication between patients and physicians improve patient satisfaction 38. In addition, patients want autonomy and a role in determination of their medical care; physicians need to be able to understand the goals and needs of patients 14,15…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, the Institute of Medicine (IOM) issued the Crossing the Quality Chasm report that emphasized the importance of taking patient’s values and preferences into account to provide high quality, patient-centered care 23. Effective and collaborative communication skills increases patient satisfaction and improves health related outcomes 38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Sahani et. al demonstrated similar finding of patients being more satisfied with their primary care physician compared to the specialized care [22].…”
Section: Discussionmentioning
confidence: 73%
“…9 Karena kepuasan pasien semakin penting dan diakui sebagai indikator yang penting untuk kualitas pelayanan, literatur mengenai diabetes kini semakin berfokus pada kualitas pelayanan dan pengukurannya. 10 Kualitas pelayanan kesehatan di Indonesia dan hubungan/kaitannya yang masih kurang dipahami memerlukan elaborasi lebih lanjut. Mengingat besarnya kontribusi penyakit diabetes dalam menyebabkan gangguan ginjal yang memungkinkan pasien dirawat pada fasilitas kesehatan tingkat lanjut, maka diperlukan data untuk mengetahui tingkat kepuasan pasien sebagai evaluasi pelayanan pengobatan yang diberikan, sebagai upaya untuk meningkatkan kualitas dari sistem pelayanan kesehatan di Indonesia, khususnya untuk pasien DMT2 dengan komplikasi ginjal yang dirawat pada fasilitas kesehatan tingkat lanjut.…”
Section: Pendahuluanunclassified